Sanksi Pidana untuk Anak Berhadapan dengan Hukum Perspektif Residivisme - Erwanto Pasaribu; Eko Agus Priadi; Try Wahyudi; Yonathan Rizky Wicaksono (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2024)
Sociologically, a child's development, both in terms of environment and mental state, determines whether a child engages in criminal behavior. The legal issue regarding criminal sanctions for children is a difficult and sensitive problem in society because children are the next generation that requires guidance and protection. The concept of recidivism becomes an important factor in the enforcement of law against children who commit violations in this situation. A person's tendency to commit a criminal act again after being previously convicted is called regression. In this discussion, we will address the criminal sanctions applied to children, their effects on recidivism, and the strategies that should be used to resolve this issue.